Progressive vitiligo, mental retardation, facial dysmorphism, and urethral duplication without chromosomal breakage or immunodeficiency. Issue 8 (August 1992) - Labrune, P; Assathiany, R; Penso, D; Odièvre, M
Abstract : A boy, born to first cousin parents of Algerian origin, first presented at the age of 9 years with growth failure, mental retardation, and dysmorphic facies. Progressive vitiligo developed from the age of 12 and distal duplication of the urethra was later recognised. The basis of this syndrome remains to be determined; autoimmune disease, chromosomal breakage syndromes, and other neurocutaneous syndromes have been excluded.